Prosedur Manajemen Arsip pada Divisi Penjualan PT. Astra Motor Center Semarang - Sigit Kamseno; Moeljono Moeljono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Archives as memory centers are documents that are very important as evidence of activities or transactions. The purpose of this research is that the writer knows the archive management process that exists at PT. Astra Motor Center Semarang. The research method used is descriptive qualitative method, with data collection techniques through field observations, interviews, and literature study. The results of this study resulted in a record management process at PT. Astra Motor Center Semarang is not running well. It can be concluded that at PT. Astra Motor Center Semarang in carrying out archive management is still not in accordance with the SOP that applies to the company.